Molecular and Integrative Physiological Effects of Isoflurane Anesthesia: The Paradigm of Cardiovascular Studies in Rodents using Magnetic Resonance Imaging - Constantinides, Christakis; Murphy, Kathy (Frontiers in Cardiovascular Medicine, 2016)
To-this-date, the exact molecular, cellular, and integrative physiological mechanisms of anesthesia remain largely unknown. Published evidence indicates that anesthetic effects are multifocal, and occur in a time-dependent and coordinated manner, mediated via central, and local, peripheral pathways. Their effects can be modulated by a range of variables, and their elicited end-effect on the integrative physiological response is highly variable. This review summarizes the major cellular and molecular sites of anesthetic action with a focus on the paradigm of isoflurane (ISO) – the most commonly used anesthetic nowadays – and its use in prolonged in vivo rodent studies using imaging modalities, such as Magnetic Resonance Imaging (MRI). It also presents established evidence for normal ranges of global and regional physiological cardiac function under ISO, proposes optimal, practical methodologies relevant to the use of anesthetic protocols for MRI, and outlines the beneficial effects of nitrous oxide supplementation.